2015
DOI: 10.5337/2015.215
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of fruit and vegetable quality: certification and other options for safeguarding public health in West Africa

Abstract: 164 Working PapersThe publications in this series record the work and thinking of IWMI researchers, and knowledge that the Institute's scientific management feels is worthy of documenting. This series will ensure that scientific data and other information gathered or prepared as a part of the research work of the Institute are recorded and referenced. Working Papers could include project reports, case studies, conference or workshop proceedings, discussion papers or reports on progress of research, country-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…A similar case was found for potatoes and cauliflower production in Pakistan (Ensink et al, 2004). Thereby, since consumers are often unaware of health risks of consuming crops irrigated with wastewater, consumers prefer crops which are larger in size and look more fresh (Keraita and Drechsel, 2015).…”
Section: Crop Productionsupporting
confidence: 61%
“…A similar case was found for potatoes and cauliflower production in Pakistan (Ensink et al, 2004). Thereby, since consumers are often unaware of health risks of consuming crops irrigated with wastewater, consumers prefer crops which are larger in size and look more fresh (Keraita and Drechsel, 2015).…”
Section: Crop Productionsupporting
confidence: 61%
“…Certification, labelling and accreditation schemes were also suggested as a way to improve the quality of food (Downs et al, 2018;Lagerkvist et al, 2018;Maitiniyazi and Canavari, 2021). These recommendations have been further explored in a review in West Africa (Keraita and Drechsel, 2015), which concluded that regulatory measures, such as certification are not the most effective measure to improve food safety due to limited or overburdened institutional capacities (Grace, 2015;WHO, 2020). Improving and upgrading food safety in LMICs is important as most of the food system relies on the informal sector, which can have a significant impact on human and economic value.…”
Section: Recommendations For Policy Actionmentioning
confidence: 99%
“…For instance, health concerns are likely to increase vegetables consumption due to its health impacts. Consuming a sufficient amount of vegetables has important health benefits, but consumers also become concerned when vegetables are contaminated through the use of agrochemicals and contaminated irrigation water in production (Bellwood-Howard et al , 2015; Keraita and Drechsel, 2015; Amoah et al , 2006, 2011). These unwholesome production practices pose human health risks when such vegetables are consumed (Sangkumchaliang and Huang, 2012; Carvalho, 2006; Amoah et al , 2006).…”
Section: Introductionmentioning
confidence: 99%